Development of stability indicating method for the simultaneous estimation of alogliptin and pioglitazone in bulk and tablet dosage form by reversed-phase ultra-performance liquid chromatography method - Ramesh Dhani, Harish Kumar Donthi Ramachandra Guptha, Deveswaran Rajamanickam (Journal of Applied Pharmaceutical Science, 2019)
The objective of the work is to develop and validate a new reverse phased ultra-performance chromatography method and its stability studies for the simultaneous estimation of alogliptin and pioglitazone in bulk and tablet dosage form. The column of the method was BEH C18 (2.1× 50 mm, 1.7 μ) used as a stationary phase and the mobile phase was 45:55 v/v of phosphate buffer (pH 3) and methanol, respectively. The injection volume was 2 μl and flow rate was maintained at 0.3 ml/minute. The wavelength was 280 nm and the runtime was 3 minutes. The retention time of alogliptin was 0.4 minutes and pioglitazone was 0.529 minutes. The Linearity of the alogliptin was 6.25–37.5 μg/ml and pioglitazone was 15–90 μg/ml. The newly developed method could be used for the routine analysis of pure drug and its formulations in accordance with the ICH Q2 (R1) guidelines.
Keywords: Alogliptin, pioglitazone, BEH C18, RP-UPLC, phosphate buffer.